Vasil Levky’s Personality and Ideology: Historical Restrospections and Contemporary Interpretations (UNWE Yearbook, 2023)
The text analyzes Levski’s personality and ideas from a historical and contemporary viewpoint. The focus is on the Apostle’s special place and indisputable role in the national liberation movement. It can firmly be stated that the most important contemporaries recognized him as the main actor in the Bulgarian revolution, a great personality with undeniable qualities, in the space of the Bulgarian Revival. The pillars in Levski’s ideology reveal him as a non-standard, Renaissance personality, for whom the individual and societal success are possible only on the basis of adequate innovation and the creative practical approach, taking into consideration the specifics of the native being. Therefore, studying the Apostle’s deed, comparing it to the other peoples’ achievements, the Bulgarian has always had the chance and today can proudly and with dignity compare themselves with the other peoples – moreover on equal footing! As any respected member of the civilizational world can. After all, what the Apostle said and did is richness not only for the Bulgarian but for the European political civilization.